Long‐term treatment outcomes in Gaucher disease. (July 2015) - Charrow, Joel; Scott, C. Ronald
Abstract : Following the treatment of the first Gaucher disease patient with enzyme replacement therapy (ERT), it was clear that ERT had the potential to be transformative with dramatic improvements in systemic manifestations of the disease within 2 years. Following over 20 years existence of the International Collaborative Gaucher Group Gaucher Registry and evidence from ∼6000 patients, the long‐term effects of therapy have been documented. It has been shown that ERT can result in improvements in all clinical and laboratory parameters of nonneuronopathic disease. However, different aspects of the disease, such as hematologic parameters, organ volumes and bone disease do not necessarily respond to therapy at the same rate or to the same extent, and this has had major implications for disease monitoring and for the establishment of therapeutic goals for ERT. Response may be affected by factors such as the timing of therapy initiation, the presence of irreversible complications such as osteonecrosis, and by enzyme dose. It is also apparent that ERT has no impact on neurological aspects of disease and highlights the need for additional or alternative treatment strategies able to meet the needs of patients with neuronopathic disease. Am. J. Hematol. 90:S19–S24, 2015. © 2015 Wiley Periodicals, Inc.